INFORMAL CAREGIVERS FOR BONE MARROW TRANSPLANTS – A QUALITATIVE STUDY ON OCCUPATIONAL LIFE: BONE MARROW TRANSPLANT CARERS – A QUALITATIVE STUDY - FERNANDES DE ANDRADE, LETÍCIA; De Carlo, Marysia Mara Rodrigues do Prado (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2024)
OBJECTIVE: To understand the experience of informal caregivers' burden related to the task of caring for people undergoing hematopoietic stem cell transplantation. METHOD: Qualitative study based on interviews with six informal caregivers of onco-hematological patients who underwent hematopoietic stem cell transplantation and were admitted to the Bone Marrow Transplant Unit of a public, tertiary hospital, located in the interior of the State of São Paulo. Participants were selected through active search and recommendation from the unit's team. After ethical approval (CAAE: 64066622.9.0000.5393, on 05/29/2023), sociodemographic characterization data were collected and the interviews were audio-recorded and fully transcribed. The MAXQDA software was used for data analysis. Participant profile data were analyzed using simple descriptive statistics and qualitative data underwent thematic analysis according to Braun & Clarke. RESULTS: Two thematic units address the impacts of overload on the informal caregiver's occupational life and coping strategies for managing overload. CONCLUSION: The informal caregiver plays an important role, but this creates an overload that impacts the treatment of the sick person. Therefore, caring for caregivers and welcoming them as subjects of care can mitigate the impacts faced by caregivers during and after the transplant process.